Analysing tourism destination promotion through Facebook by Destination Marketing Organizations of India. Issue 9 (3rd May 2022) - Kumar, Prem; Mishra, Jitendra Mohan; Rao, Yedla Venkata
ABSTRACT: Today, the promotion of tourism destinations is evident through social media as tourists have become content creators and influencers. Destination Marketing Organizations (DMOs) promote destinations through various social media platforms of which Facebook, Twitter, and YouTube are common. Of these platforms, Facebook is widely used for promotion, consumer research, and customer service, which makes it the foremost choice of DMOs for destination promotion. In India, the State and Union Territory tourism departments act as DMOs. The study explores how Indian DMOs strategically employ Facebook to promote their destinations. Six months' data were collected from the Facebook pages of 32 DMOs for content analysis. Semi-structured interviews were conducted with seven managers of tourism departments. The Jammu and Kashmir and Kerala DMOs have shown high user engagement through firm-generated content (visual content and informative posts). The findings conclude that DMOs are using Facebook as a supplement to traditional marketing tools and rarely for customer service and research. DMOs benefit from the contents of scenic beauty, culture, and cuisine which appeal more to engage users on Facebook pages. Further, implications for management and managerial actions have been suggested.